Physical activity and its influence on the quality of life of penitentiary agents (Research, Society and Development, 2022)
Objective: To analyze the practice of physical activity and its influence on the quality of life of prison officers. Method: Research carried out with prison officers in the city of Jequié/Ba. The reporting of demographic data through the bioelaborated by the investigation. To test the level of physical activity and quality of life from the IPAQ and quality of life from the WHOQOL-bref. Data were tabulated and analyzed using SPSS version 210. As categorical variables through frequencies and as intervals through measures of central tendency and dispersion, 95% confidence was used (p